Social media use, socialization, and perceptions of syrians among turkish youth: findings from a national survey - (:unkn) unknown (My University, 2022)
Young people\"s attitudes towards Syrians will play a decisive role in Turkish society\"s future as a significant proportion of the population consists of Syrians today. As of June 2022, there are approximately 3,7 million Syrians in Turkiye. The literature shows that social media and socialization are important factors affecting individuals\" attitudes towards immigrants. This article explores how (1) the amount of time spent on social media, and (2) self-reported adequate socialization in daily life affect perception toward Syrian immigrants among young adults in Turkiye. We used data from the Turkish Youth Survey (TYS), which was conducted in 2018 by interviewing 7,949 individuals between the ages of 18 and 30. We measured anti-immigrant perception by using answers given to the question of whether the study participants would live in the same neighborhood as Syrians. The findings indicate that young adults become less open to the idea of living with the Syrian immigrants in the neighborhood as they spend more time on social media. We also find that those who say they are adequately socializing in their daily lives are less likely to say they do not want to live in the same neighborhood as Syrian immigrants.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Genel Sosyoloji ve Metedoloji; Social Sciences and Humanities; Sociology; General Sociology and Methodology; SOSYOLOJİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); SOCIOLOGY; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Sosyoloji ve Siyaset Bilimi; Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Sociology and Political Science; General Social Sciences; Social Sciences & Humanities; Social media use; socialization; anti-immigrant attitudes; Syrians in Turkiye; youth